Patient factors associated with SARS‐CoV‐2 in an admitted emergency department population. Issue 4 (13th June 2020) - Haimovich, Adrian D.; Warner, Frederick; Young, H. Patrick; Ravindra, Neal G.; Sehanobish, Arijit; Gong, Guannan; Wilson, Francis Perry; van Dijk, David; Schulz, Wade; Taylor, Richard Andrew
Abstract: Background: The SARS‐CoV‐2 (COVID‐19) virus has wide community spread. The aim of this study was to describe patient characteristics and to identify factors associated with COVID‐19 among emergency department (ED) patients under investigation for COVID‐19 who were admitted to the hospital. Methods: This was a retrospective observational study from 8 EDs within a 9‐hospital health system. Patients with COVID‐19 testing around the time of hospital admission were included. The primary outcome measure was COVID‐19 test result. Patient characteristics were described and a multivariable logistic regression model was used to identify factors associated with a positive COVID‐19 test. Results: During the study period from March 1, 2020 to April 8, 2020, 2182 admitted patients had a test resulted for COVID‐19. Of these patients, 786 (36%) had a positive test result. For COVID‐19‐positive patients, 63 (8.1%) died during hospitalization. COVID‐19‐positive patients had lower pulse oximetry (0.91 [95% confidence interval, CI], [0.88–0.94]), higher temperatures (1.36 [1.26–1.47]), and lower leukocyte counts than negative patients (0.78 [0.75–0.82]). Chronic lung disease (odds ratio [OR] 0.68, [0.52–0.90]) and histories of alcohol (0.64 [0.42—0.99]) or substance abuse (0.39 [0.25—0.62]) were less likely to be associated with a positive COVID‐19 result. Conclusion: We observed a high percentage of positive results among an admitted ED cohort under investigation for COVID‐19. Patient factors may be useful in early differentiation of patients with COVID‐19 from similarly presenting respiratory illnesses although no single factor will serve this purpose.